2022
DOI: 10.1039/d2dt00163b
|View full text |Cite
|
Sign up to set email alerts
|

Copper peroxide coated upconversion nanoparticle modified with glucose oxidase for H2O2self-supplying starvation-enhanced chemodynamic therapyin vitro

Abstract: Chemodynamic therapy (CDT) can convert endogenous hydrogen peroxide (H2O2) to highly reactive hydroxyl radical (•OH) through Fenton or Fenton-like reaction to kill tumor cells, which is a promising anticancer strategy....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The color variation of KMnO 4 (50 μg ml −1 ) in acidic media can be used for qualitative analysis of the generation of peroxy groups (•OH). [34] Circular membrane specimens (Φ = 10 mm) were infiltrated with 1 mL acidic KMnO 4 for 30 min, and the absorbance at 520 nm was measured by a UV-vis spectrophotometer (AOE, UV-1000).…”
Section: Colorimetric Assessment For Peroxy Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The color variation of KMnO 4 (50 μg ml −1 ) in acidic media can be used for qualitative analysis of the generation of peroxy groups (•OH). [34] Circular membrane specimens (Φ = 10 mm) were infiltrated with 1 mL acidic KMnO 4 for 30 min, and the absorbance at 520 nm was measured by a UV-vis spectrophotometer (AOE, UV-1000).…”
Section: Colorimetric Assessment For Peroxy Groupsmentioning
confidence: 99%
“…[30,31] Moreover, Cu 2+ has been reported to simulate hypoxia in wound sites, contributing to the stabilization of hypoxia-inducible factor (HIF-1𝛼) and the expression of downstream-targeted genes, including vascular endothelial growth factor (VEGF), which enhances angiogenesis and promotes wound healing. [32] While n-CuO 2 has expressed some promising applications in CDT for cancer treatment, [33][34][35] its applications for chronic wound healing are still in their infancy. [36] To date, very few studies have reported the potential of PCL-based EUFs for enhancing angiogenesis within diabetic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Two biological processes have been employed recently to produce H 2 O 2 in tumors. First, glucose oxidase (GO x ) is used to accelerate the reaction of water, oxygen, and glucose to form gluconic acid and H 2 O 2 [151]. Te alternative process uses superoxide dismutase (SOD) to catalyse the production of H 2 O 2 from superoxide anion radicals [150].…”
Section: Improved Chemodynamic Terapy Chemodynamic Therapy (Cdt) Is A...mentioning
confidence: 99%
“…15 GO x can catalyze glucose to produce gluconic acid and H 2 O 2 . 17 Thus, in the presence of glucose, the bimetallic Al/Fe-based NMOF loaded with GO x will decrease the pH value of the bacterial infection microenvironment and avoid the addition of exogenous H 2 O 2 . 18…”
Section: Introductionmentioning
confidence: 99%